Training Technologies as Means for Forming the Professional Identity of Police Officers during Professional Genesis (Law and Safety, 2020)
One of the modern technologies for training and developing individuals is a variety of trainings, including professionally-oriented ones. Since the training of modern police officers in higher educational institutions with specific learning conditions should focus on professional self-development of personality, formation and development of professional identity and other necessary personal and professional qualities, the aim of the study was to identify the effectiveness of training procedures on the dynamics of professional identity. Modern concepts of professional genesis, psychological theory of activity and the concept of genetic development of personality became the methodological basis of the study.It is noted that the developed and worked out program of comprehensive training to optimize the professional genesis of the employees of preventive units of the National Police consists of three modules and allows participants to solve problems (professional and life) situations during training exercises. It was found out that the training expands the knowledge of cadets on the professional identity of police officers, helps to deepen their knowledge of the prerequisites for professional formation and development, outlines their priorities in professional activities.It is established that after the training there is a positive dynamics of growth of both the level of professional identity of cadets in the whole and its individual components. In particular, the design-behavioral and motivational-value components of professional identity have been changed, which indicates about a clearer assessment of cadets’ professional plans, as well as clarity, independence in the process of building them, the desire to remain in the profession and to be successful there. The author has noted the cadets’ need for self-realization, the conformity of their personal and life values to the values of the profession and the professional community, the value of the chosen profession for them, the established emotional attitude of cadets to the chosen police profession and to themselves as its representative.It is expedient to use the received results of the research for drawing up the programs of psychological support of police officers at various stages of the professional genesis.
Keywords: training; cadets; police; professional identity; professional activity; professional genesis; профессиональная деятельность